Prevalence and Severity Level of Low Back Pain at Citra Indah Konveksi Tailors In Tabanan - Dhania, A.A. Putri Risma; Ayu Widianti, I Gusti; ., Muliani; ., Yuliana (E-Jurnal Medika Udayana; Vol 12 No 12 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i12.P17, 2023)
The human need for clothing is increasing and developing over time. This also has an impact on convection tailors because convection tailors work in the same position for a long period of time and ultimately cause impacts such as low back pain in the future. This study aims to determine the prevalence dan severity level of low back pain in Citra Indah Konveksi tailors. The research design is descriptive observational with cross-sectional design where data collection is only done once for each respondent using primary data from a questionnaire. A total of 14 respondents were selected by purposive sampling or by considering inclusion and exclusion. The results of this study showed that of the 14 respondents who were included in the inclusion criteria, low back pain had the greatest incidence in female respondents (55.5%), with normoweight and obese BMI (33.3%), age range 41-55 (66,6%). Most of the were experiencing non radiating pain (55,6%), acute low back pain (88,9%), and they are in category of mild disability (55,6%). Respondents who were included in the inclusion criteria in this study, there were 9 respondents (64,2%) experienced low back pain and who had a severity level with no disability of 2 respondents (11.1%), mild disability of 5 respondents (55.6%), moderate disability of 1 respondent (11.1%), severe disability of 1 respondent (11.1 %). Keywords: Low Back Pain, Prevalence, Convection tailors